Digital and social interaction: a systematic literature review of TikTok's appeal via Uses and Gratifications Theory - Du, Shengwei; Hashim, Norliana; Kamarudin, Syafila (Elite Scientific Publications, 2024)
Needs and satisfaction have always been important for researchers in understanding human behavior, motivation and happiness. When a person's needs are met, he will feel satisfied. People usually use social media to achieve this need. If it is not met, people will have negative emotions such as depression and anxiety. Researchers strive to adjust people's emotions through theory to satisfy users. The most widely used is Uses and Gratifications Theory (UGT). This study adopts a systematic literature review method and uses Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) to analyze existing literature. This paper selects Science Direct and Scopus databases, with a time limit of 2015 to 2024, and selects 36 papers according to the screening criteria. This paper analyzes the origin and development of Uses and Gratifications Theory and analyzes why this theory is suitable for studying user needs and satisfaction. This paper takes undergraduates as the analysis object and TikTok as the research media and summarizes the primary needs as information needs, social needs, personal integration, social integration, entertainment needs, and convenience motivation. Entertainment needs are the most important needs of undergraduates, while information needs are the least important needs of undergraduates. The short and sophisticated video content and personalized algorithm push in TikTok are the main reasons for users’ addiction. The adolescent group that has used social media for a long time is an important direction for future research groups. This paper can also help social media technicians to improve the functions of the media continuously, strive to meet the different needs of users, and then increase the number of users and expand the scale of the enterprise. At the same time, this paper also provides certain conclusions and effective data for future research on UGT and the expansion of the theoretical framework. © (2024), (Elite Scientific Publications). All rights reserved.